A mystery revealed: an update on eosinophil and other blood cell morphology of the Argentine black and white tegu (Salvator merianae) - Bosch, Sarah N.; Stacy, Nicole I.; Armien, Anibal G.; Hollinger, Charlotte; Minor, Rashea; Heard, Darryl J.; Stokol, Tracy (Frontiers in Veterinary Science, 2024)
Reptile white blood cell (WBC) morphological features are strikingly variable across species. In the Argentine black and white tegu (Salvator merianae), red tegu (Salvator rufescens), and Savannah monitor (Varanus exanthematicus), previous reports described a WBC type with a single distinct, clear, linear to ovoid to crescent-shaped inclusion of presumptive monocytic origin. The objective of this report was to further investigate the origin of this unique WBC type with crescent-shaped inclusions. Blood samples from two Argentine black and white tegus, tegu 1, a 4-year old female, and tegu 2, a 2-year old presumed male were submitted for routine hematological evaluation. Additional blood films were prepared and stained with these cytochemical stains: alkaline phosphatase (ALP; naphthol AS-MX phosphate substrate), alpha-naphthyl butyrate esterase, alphachloroacetate esterase, myeloperoxidase, Periodic-acid Schiff, and Sudan black B. Blood films from tegu 1 were also stained with a second ALP stain (5-bromo-4-chloro-3-indoxyl-phosphate and nitroblue tetrazolium substrate), Luna, luxol fast blue, and toluidine blue. The blood from tegu 1 was cytocentrifuged to isolate and fix the buffy coat in glutaraldehyde 2.5% aqueous solution for transmission electron microscopy. Six morphologically distinct WBC types were identified from tegu 1, including heterophils, basophils, monocytes, azurophils, lymphocytes, and the unique WBC type which were identified as eosinophils with inclusions. WBC types in tegu 2 were similar, however, eosinophils lacked a discernable inclusion. Proper WBC identification will be useful to obtain accurate hemogram data in this species.